ANALISIS PERANCANGAN SISTEM INFORMASI PUSAT DATA DAN INFORMASI (PUSDATIN) DOSEN FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PANCASAKTI TEGAL - susilawati, agnes dwita; Prihadi, Deddy; Irawan, Bei Harira; Rahmatika, Dien Noviany; Saputra, Rikky (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2024)
The use of computers as one of the information technology tools is very much needed in almost every aspect of life. Higher education is currently required to follow the rapid developments in all fields, where these developments require an increase in quality in achieving its goals. The data processing activities in question are in the form of writing activities, storing files, grouping files which are organizational routines that will certainly drain time and space. Data in the form of hard copies are often not neatly arranged according to their groups. Therefore, a system is needed where data can be grouped, processed and stored into a system. The system development model used in this study uses the System Development Life Cycle method. The Research Methodology uses Observation, Interviews and Literature Studies, design process, analysis process and conclusion and suggestion process